1983
DOI: 10.1097/00000658-198305000-00009
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Calcifications as the Only Basis for Breast Biopsy

Abstract: Two hundred fifty-one consecutive patients were treated between 1964 and 1982 with mammographic calcifications as the only reason for breast biopsy. Patients with either clinical or x-ray findings other than calcifications were excluded. A correlation of the x-ray, pathology, and clinical experience is the basis of this report. Specimen radiography with paraffin section histology (i.e., no frozen section) was performed on all biopsy material. The procedure of specimen radiography that was utilized is described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Benign breast calcifications are smooth, round, dense, and scattered over a large area, whereas malignant calcifications show clustered or linear morphology or can be large and pleomorphic, even though overlap exists [13,14]. Many authors have reported that the number of calcifications within an area is an important parameter of clustered calcification, indicating that when the number of calcification is low (less than 5 per 0.25 cm 2 ), less than five per cluster, or when present in loose cluster, the lesions are very unlikely to be malignant [15][16][17]. There are two processes in which calcifications are formed in the breast: secretory type, which is related to secretion accumulation, and hence likely to be found in benign lesions or low grade malignancies; and necrotic type caused by rapidly proliferating tumor cells depleted of vascular supply found in comedo necrosis [18].…”
Section: Discussionmentioning
confidence: 99%
“…Benign breast calcifications are smooth, round, dense, and scattered over a large area, whereas malignant calcifications show clustered or linear morphology or can be large and pleomorphic, even though overlap exists [13,14]. Many authors have reported that the number of calcifications within an area is an important parameter of clustered calcification, indicating that when the number of calcification is low (less than 5 per 0.25 cm 2 ), less than five per cluster, or when present in loose cluster, the lesions are very unlikely to be malignant [15][16][17]. There are two processes in which calcifications are formed in the breast: secretory type, which is related to secretion accumulation, and hence likely to be found in benign lesions or low grade malignancies; and necrotic type caused by rapidly proliferating tumor cells depleted of vascular supply found in comedo necrosis [18].…”
Section: Discussionmentioning
confidence: 99%
“…The definition of clustered calcification is taken as more than 5 microcalcifications in an area of 1 cm 2 , or an area of 0.5 cm · 0.5 cm or in the volume of 1 cc [42][43][44].There is however considerable overlap between benign and malignant lesions with clustered calcifications, making this morphological description somewhat non discriminatory (Figs. 3, 4).…”
Section: Clustering Of Calcificationsmentioning
confidence: 99%
“…To enhance the discriminatory power of clustered calcification, many authors have reported that the number of calcifications within an area is an important parameter of clustered calcifications. When the number of calcification is low (less than 5 per 0.25 cm 2 [43], or less than five per cluster [44], or when the calcifications are present in a loose cluster [45]), the lesions are very unlikely to be malignant. In addition, other associated parameters have been reported to be important in predicting malignancy, and these include pleomorphism of the calcification, architectural distortion, associated mass and associated density.…”
Section: Clustering Of Calcificationsmentioning
confidence: 99%
“…Age at first birth, y* 10-20_12 (15)_2 (7) 20-30_53 (68)_18 (64) 30-40_13 (17)_7 (25) >40_0 (0)_1 (4) No. of pregnancies 0 94 (54) 39 (59) t-2_27 (16)_13 (20) 3-4_38 (22)_7 (11) 5-6_11 (6)_4 (6) >6_3 (2)_3 (4) Prior breast problems 41 (24) 18 (27) Family history_28 (16)_11 (17) White_154 (89) The site of origin of all lesions was reviewed (Fig 1) …”
mentioning
confidence: 99%